Relatório do estágio curricular supervisionado em Medicina Veterinária- área: clínica e cirurgia de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This report describes the activities carried out by the academic Anna Luiza Machado Sampaio during the Supervised Curricular Internship in Medicine Veterinary (ECSMV), in the area of clinic and surgery in small animals, under the guidance from Prof. Dra Maria Ligia de Arruda Mistieri. The internship was carried out initially at the Veterinary Clinical and Surgical Center, under the supervision of the Veterinarian (MV) Marco Aurélio Avendano Motta, in the city of Pelotas / RS, in period from 08/03/2015 to 09/04/2015, comprising 200 (two hundred) practical hours. From 09/08/2015 to 11/06/2015, the internship was held at Dr. Guilherme Savassi Surgical Clinic for Dogs and Cats, in Belo Horizonte / MG, under supervision Dr Guilherme Savassi, totaling 336 (three hundred and thirty-six) hours. In total, 536 (five hundred and thirty-six) hours of practical training were carried out. At end, three cases of interest will be reported accompanied by the student in this period: 1) Therapeutic ovariohysterectomy in canine by video laparoscopy. 2) Persistence of Right Aortic Arch in a dog. 3) Avascular necrosis of the femoral head in a dog.
Report of the supervised curricular internship in Veterinary Medicine - area: clinic and small animal surgery
Keywords: Medicina veterinária; Clínica de pequenos animais; Veterinary medicine; Small animal clinic; Cirurgia de pequenos animais; Small animal surgery; CNPQ::CIENCIAS AGRARIAS